Mucous membrane pemphigoid and oral blistering diseases. (18th May 2019) - Carey, B.; Setterfield, J.
Summary: The autoimmune blistering disorders present with variable frequency in the oral cavity. Recognition of their key clinical features at presentation is important, as there are many causes of oral ulceration. Careful history‐taking, clinical examination, an understanding of pathogenesis and appropriate investigations are essential. With the exception of the rare genodermatoses that may lead to blistering and oral ulceration, the majority of patients have an acquired disorder. These include the rare autoimmune blistering diseases mucous membrane pemphigoid (MMP), pemphigus vulgaris (PV), linear IgA disease, epidermolysis bullosa acquisita and paraneoplastic pemphigus. Important clinical differential diagnoses include erythema multiforme, which may be mistaken for PV in appearance, while oral lichen planus may be indistinguishable from MMP. Angina bullosa haemorrhagica may also present with tense haemorrhagic bullae, and in the absence of diagnostic tests, requires an astute clinical diagnosis based upon the history. Newer laboratory techniques have facilitated identification of target antigens and epitopes in the autoimmune blistering diseases, particularly in MMP. Current interest is in whether these relate to clinical presentation and outcomes. There have also been recent investigations into the use of saliva as an alternative medium to serum for the diagnosis of oral vesiculobullous lesions. Assessment of disease severity and measurement of quality of life at presentation and subsequent follow‐up is paramount to interpreting therapeutic response. Furthermore, combining these scores with serological and/or salivary biomarkers is valuable in the assessment of clinical response. In this paper, we discuss MMP and its important differential diagnoses. Abstract : Click here for the corresponding questions to this CME article.